The Role of English as a Global Language in Modern Communication (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides a comprehensive analysis of the role and significance of the English language in modern global communication. In the context of rapid globalization, English has become the primary means of communication connecting people from different nations and cultural backgrounds. The paper examines the historical development of English and the political, economic, and cultural factors that have contributed to its global spread. In addition, the role of English in education, science, business, diplomacy, and digital technologies is analyzed, while the impact of English language dominance on multilingual societies and the challenges it creates are discussed.